Enhancing Elementary School Students’ Creative Thinking and Engagement through the ARIAS Learning Model Assisted by Wordwall - Diana Puspitasari; Yanuarto, Wanda Nugroho (Mathematics Research and Education Journal, 2026)
This study examined the effectiveness of the ARIAS learning model (Assurance, Relevance, Interest, Assessment, and Satisfaction) assisted by Wordwall in improving elementary students’ creative thinking and engagement in mathematics learning, particularly on equivalent fractions. The study employed a quantitative quasi-experimental design with a nonequivalent control group. The participants consisted of 42 fourth-grade students from two public elementary schools in the Diponegoro cluster, Sumbang District, Banyumas Regency, with 21 students in the experimental class and 21 students in the control class. Data were collected through essay tests, observation sheets, and student engagement questionnaires. The results showed that students taught using the ARIAS model assisted by Wordwall achieved higher creative thinking scores (M = 86.48, SD = 8.02) than students in the control class (M = 74.00, SD = 5.33), with a significant difference (p < .001). Student engagement was also significantly higher in the experimental class (M = 88.57, SD = 5.86) compared to the control class (M = 69.81, SD = 5.89). These findings indicate that the ARIAS learning model assisted by Wordwall effectively enhances both creative thinking and student engagement in elementary mathematics learning.